Marketing verde e práticas socioambientais de produtores de cogumelos no estado de São Paulo - Ronchesel, Murilo (2017)
The objective of this research is to establish the typology of the rural producers of edible mushrooms of the State of São Paulo and the production systems practiced by them. In addition, to analyze the strategies of dissemination of the production, from the perspectives of the Green Marketing, under the paradigm of sustainability. The research method used to perform qualitative research was the type of survey, which is used when the research object is to identify opinions, attitudes, values, perceptions, it is possible to use the survey method to collect data and information. The research was carried out through a questionnaire made available on the Internet, and the questionnaire was fully programmed in the tool, with all the structure of the logic of the questions and answers, which minimizes possible logic errors of the questions. After the parameterization, the system generates a virtual address with all the questions to be answered. The results of the research showed an increased concern on the part of producers for the adoption of socio-environmental practices and green marketing in the process of dissemination of their products.